2010
DOI: 10.1111/j.1095-8649.2009.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Na+–H+ exchanger isoforms (NHE2) in the gills of the euryhaline teleost Fundulus heteroclitus

Abstract: In the current study, reverse-transcription polymerase chain reaction (RT-PCR) and rapid amplification of cDNA ends (RACE) PCR were used to clone full-length putative Na(+)-H(+) exchanger isoforms (NHE2a) cDNA from the gills of Fundulus heteroclitus. The 2480 bp cDNA includes a coding region for a protein that shows a 57% amino acid homology to rabbit NHE2. These sequences allowed data mining of available fish genome data, which revealed at least three NHE2 subtypes in some teleost species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…No nhe1 expression difference between SW and FW has been shown in the rainbow trout in different tissues including gills, kidney and anterior intestine (Genz et al, 2011). Few studies have quantified the expression of different nhe2 paralogs, notably nhe2c (Edwards et al, 2010). We have identified three nhe2…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 3 more Smart Citations
“…No nhe1 expression difference between SW and FW has been shown in the rainbow trout in different tissues including gills, kidney and anterior intestine (Genz et al, 2011). Few studies have quantified the expression of different nhe2 paralogs, notably nhe2c (Edwards et al, 2010). We have identified three nhe2…”
Section: Accepted Manuscriptmentioning
confidence: 91%
“…are not expressed in the posterior kidney and intestine and nhe2a was not clearly detected in any osmoregulatory tissue. This is not the case in killifish, where NHE2a has been identified in cuboidal cells, the cell type expressing basolateral VHA and being involved in Na + uptake (Edwards et al, 2010;Laurent et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
See 2 more Smart Citations
“…B. Claiborne and colleagues, working at the MDIBL, who demonstrated that recovery from induced acidosis in the longhorn sculpin was inhibited by low external Na + concentrations (20–30 mM) or by external amiloride [or the more Na/H-specific 5- N , N -hexamethylene-amiloride (HMA)] (Claiborne and Evans, 1988). These physiological data were corroborated by subsequent molecular data showing immunolocalization of Na + /H + exchanger isoforms (NHEs), and V-H + -ATPase, in the gill epithelium of the sculpin in seawater (Claiborne et al, 1999; Catches et al, 2006), and this gill localization of NHEs has now been extended to the little skate (Choe et al, 2002), spiny dogfish (Tresguerres et al, 2005; Choe et al, 2007), and killifish (Claiborne et al, 1999; Choe et al, 2002; Edwards et al, 2010) at the MDIBL. V-H + -ATPase and a Cl − /HCO3 exchanger (pendrin) have also been immunolocalized in the gill epithelium of the Atlantic stingray in seawater (Piermarini and Evans, 2001; Piermarini et al, 2002).…”
Section: Evolutionary Origin Of Nacl Uptake Mechanisms In Freshwater mentioning
confidence: 99%